2011
DOI: 10.1063/1.3633522
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AlN buffer layer properties on the morphology and polarity of GaN nanowires grown by molecular beam epitaxy

Abstract: Low-temperature AlN buffer layers grown via plasma-assisted molecular beam epitaxy on Si (111) were found to significantly affect the subsequent growth morphology of GaN nanowires. The AlN buffer layers exhibited nanowire-like columnar protrusions, with their size, shape, and tilt determined by the AlN V/III flux ratio. GaN nanowires were frequently observed to adopt the structural characteristics of the underlying AlN columns, including the size and the degree of tilt. Piezoresponse force microscopy and polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 29 publications
6
85
0
Order By: Relevance
“…Brubaker et al 43 showed that the AlN buffer layer growth has significant impact on the morphology and polarity of GaN nanorods, which the GaN nanorods were frequently observed to adopt the structural characteristics of the underlying AlN columns, including the size and the degree of tilt. The GaN nanorods are found to be with Ga-polarity and the GaN matrix has the same polarity of the underlying low temperature AlN buffer layer, depending on the growth condition.…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Brubaker et al 43 showed that the AlN buffer layer growth has significant impact on the morphology and polarity of GaN nanorods, which the GaN nanorods were frequently observed to adopt the structural characteristics of the underlying AlN columns, including the size and the degree of tilt. The GaN nanorods are found to be with Ga-polarity and the GaN matrix has the same polarity of the underlying low temperature AlN buffer layer, depending on the growth condition.…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
“…39 A similar growth model of nanorod morphology depending on the MBE system geometry was also proposed by Galopin et al 40 In the last 2 years, the polarity of GaN nanorods became an attractive topic. [41][42][43][44][45] To determine the polarity of the GaN nanorods, many methods were employed, for example, convergent beam electron diffraction (CBED), 46,47 electron energy loss spectra (EELS), 48 probe Cs corrected transmission electron microscopy measurement, 49 Kelvin probe force microscopy (KPFM), 50 piezoresponse force microscopy (PFM), 51 coaxial impact-collision ion scattering spectroscopy (CAICISS) analysis, 52 circular photogalvanic effect (CPGE), 53 and wet chemical etching. 54 Most of them are also suitable for polarity measurement of the nanorod structure.…”
Section: B Catalyst-free Gan Nanorod Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports show that dislocations and plastic relaxation were necessary [15][16][17][18] for the nucleation. However, reports based on the observations of the polarity of nanorods suggested that nanorods were formed as a continuation of underlying pedestals, 8,12,19 as evidenced from the statistics of the rod-diameters in comparison with the underlying island-diameters.…”
Section: Nucleation Of Single Gan Nanorods With Diameters Smaller Thamentioning
confidence: 99%
“…Ga-polar, 20 N-polar, 12,21,22 or the coexistence of both polarities 19,23 of nanorods have all been reported. Direct evidence other than the rod-polarity is therefore needed to clarify the origin of the nucleation mechanism.…”
Section: Nucleation Of Single Gan Nanorods With Diameters Smaller Thamentioning
confidence: 99%